2022
DOI: 10.1136/emermed-2020-210271
|View full text |Cite
|
Sign up to set email alerts
|

Tendency to call an ambulance or attend an emergency department for minor or non-urgent problems: a vignette-based population survey in Britain

Abstract: BackgroundThere are concerns about high levels of demand for emergency health services. The aim was to identify the characteristics of the British population with a tendency to contact emergency medical services and EDs for minor or non-urgent problems.MethodsA survey of the British adult population in 2018. Six vignettes were constructed about illness in adults (cough/sore throat or diarrhoea/vomiting), injury in adults (sore rib or back pain) and fever in children (occurring weekday or weekend).ResultsThe re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…20 Access to timely care is one key reason that patients choose to attend the ED for more minor problems. 161,162 Our marker conditions analysis suggested that people most likely to have minor problems (requiring no investigations or treatment) would be seen in a more timely fashion by GPs than by ED clinicians. However, this impact did not extend beyond this small proportion of overall ED attendances to influence LOS in the ED for the whole department.…”
Section: Patient Satisfactionmentioning
confidence: 95%
See 1 more Smart Citation
“…20 Access to timely care is one key reason that patients choose to attend the ED for more minor problems. 161,162 Our marker conditions analysis suggested that people most likely to have minor problems (requiring no investigations or treatment) would be seen in a more timely fashion by GPs than by ED clinicians. However, this impact did not extend beyond this small proportion of overall ED attendances to influence LOS in the ED for the whole department.…”
Section: Patient Satisfactionmentioning
confidence: 95%
“…162 While patient-reported reasons for attending EDs are often related to limited or poor access to primary care, an analysis of routine data found that there was no statistically significant relationship between the number of GPs in a primary care trust area and the number of emergency admissions. 162,173 While patient-reported reasons for attending EDs are often related to limited or poor access to primary care, an analysis of routine data found that there was no statistically significant relationship between the number of GPs in a primary care trust area and the number of emergency admissions. 173 However, in deprived areas, a higher number of GPs was associated with reduced emergency admission.…”
Section: Patient Safety Implicationsmentioning
confidence: 99%
“…As over half of older people accessing ED are admitted to a ward,9 and prolonged hospitalisation in this population are associated with adverse risks12 and future re-admissions,13 rapid assessment and treatment models of care could be beneficial for global public health systems that are experiencing high ED usage in general,1 2 but also specifically in terms of treating older people 3–5. The introduction of specialised geriatric urgent care services could also improve patients and relatives user experience and may mitigate some of the concerns older people report regarding accessing acute care 7…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, emergency healthcare demands are increasing,2 with older Australians disproportionately presenting to ED for non-emergency conditions compared with other age groups 3. This trend appears to be international 4 5. A large proportion of older people have reported negative experiences with EDs, leading to a reluctance to re-attend 6–8.…”
Section: Introductionmentioning
confidence: 99%